The Impacts of Changes in Anthropogenic Emissions Over China on PM2.5 Concentrations in South Korea and Japan During 2013–2017 - Xie, Peifu; Liao, Hong (Frontiers in Environmental Science, 2022)
We applied the global 3-D chemical transport model GEOS-Chem to examine the effects of changes in anthropogenic emissions over China on PM2.5 concentrations in South Korea and Japan over 2013-2017 during which the Chinese governmental “Action Plan on the Prevention and Control of Air Pollution” was implemented. The reductions in anthropogenic emissions in China alleviated PM2.5 concentrations in South Korea and Japan. The reductions in anthropogenic emissions in China (FIXEM_KJ minus FIXEM_CKJ) over 2013-2017 alone led to reductions in annual mean PM2.5 concentrations by 13.7 μg m-3 (19.7%), 2.7 μg m-3 (7.7%), and 1.0 μg m-3 (7.9%) in eastern China, South Korea, and Japan, respectively. The reductions in anthropogenic emissions in China also changed the components of PM2.5 in South Korea and Japan. over 2013-2017, concentrations of sulfate, ammonium, BC and OC were simulated to decrease and those of nitrate were simulated to increase in both South Korea and Japan. With the changes in anthropogenic emissions in China and the changes in meteorology (BASE simulation), the proportions of sulfate, nitrate, and OC in PM2.5 in South Korea (Japan) were, respectively, 17.1%, 44.4%, and 15.8% (27.2%, 30.5%, and 20.0%) in 2013, and 14.3%, 46.0%, and 17.8% (23.7%, 33.2%, and 21.6%) in 2017. Model results shown here are helpful for understanding the temporal evolution in PM2.5 on different timescales in the downwind regions of China.